Cymbella liyangensis sp. nov., a new cymbelloid species (Bacillariophyceae) from streams in North Tianmu Mountain, Jiangsu province, China - Zhang, Wei; Jüttner, Ingrid; Cox, Eileen J.; Chen, Qiao; Tan, Hongxin (Phytotaxa, 2018)
During a survey of freshwater diatoms from streams in North Tianmu Mountain, Liyang City, Jiangsu Province, China, a new Cymbella species, Cymbella liyangensis sp. nov. was recorded. A detailed morphological description of C. liyangensis is presented, based on light and scanning electron microscopy. The main features of C. liyangensis are: moderately dorsiventral, semi-lanceolate valves with broadly to obtusely rounded ends; indistinct central area on the dorsal side, bordered by 1–2 shorter central striae; three or four round, different-sized stigmata open at the ends of the central ventral striae; a “ridge like” structure is present at the junction of the valve face and mantle around the valve; a marked tendency to develop biseriate striae, with up to 10 biseriate striae near the apices. The new species is compared with C. hubeiensis, C. sumatrensis, C. tridentina, C. parva, C. rumrichae, C. hantzschiana and C. vulgata, all of which show similarities to Cymbella liyangensis but differ in details of size, valve shape, stria density and structure, and number of stigmata. The species is common to abundant on stones from relatively clean stream waters from North Tianmu Mountain.